Identifikasi Potensi Bahaya Dan Pencegahan Kecelakan Kerja Bekisting Pada Pekerjaan Proyek Pembangunan Gedung Bahasa - Putri Melati Sukma Halid; Moh Yusuf Tuloli; Beby Sintia Dewi Banteng (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The Language Office Building Construction Project in Gorontalo Province primarily focuses on Occupational Health and Safety (OHS), aiming to prevent work accidents, injuries, or illnesses caused by factors such as machinery, chemicals, the work environment, and human actions. this study aimed to identify potential hazards, asses the risk of work accidents, and analyze preventive measures for accidents during the formwork installation activities. The methodology employed was a semiquantitave risk analysis method, referencing AS/NZS 4360:2004, and the data were analyze using the Statistical Package for the Social Sciences (SPSS). Based on the data analysis, identifying potential hazards and the risk of work accident in the formwork installation, reinforcing, and concrete pouring activities at the Language Office Building revealed that only a few hazards were deemed acceptable. This was attributed to a lack of awareness regarding using Personal Protective Equipment (PPE) and limited knowledge about workplace safety, despite the availability of PPE. The preventive action identified in the study fell into the “Substantial” risk category, with a risk value of 90, which could be reduced to “acceptable” levels through control such as providing shock absorbers, conducting biannual medical check-ups, and enhancing supervision and worker awareness regarding the proper use of PPE.